Alternative Batik - the potential of its outcome and designing methods / Mohd Azhar Samin, Rafeah Legino and Rabiatuadawiyah Kari - Samin, Mohd Azhar; Rafeah, Legino; Kari, Rabiatuadawiyah (Universiti Teknologi MARA, 2018)
The Malaysian batik industry can be further expanded by exploring new batik-producing methods which completely differ from conventional age-old practices. Nowadays, the society has more access to various forms of batik designs, especially those which are fresh and versatile. Therefore, there is a need for more options in the production of unique local batik designs to meet the needs and preferences of contemporary societies. To identify whether new batik designs will be widely accepted, the methodology of this study has included a textile design practice session along with a survey. Various types of materials and tools have been experimented on to create new batik designs via various techniques, and these have been compared with those of traditional batik. A questionnaire was also distributed to the batik practitioners to obtain their feedback. The results are hoped to be able to facilitate the growth of Malaysian batik in tandem with global trends. These outcomes can also be implemented theoretically and practically in the curricula of art and design courses of higher learning institutions. The establishment of alternative batik-producing methods will provide additional options for batik producers as well.